What's it like to live in.......? : Jamaica - Brownlie, Ali (London Hodder Wayland, 2003)
Shows you what the landscape, weather, transport, farming, food, shopping, houses, working life, festivals and having fun is like in Jamaica. This work includes a large, colour map of Jamaica with an inset map showing its position in the world. It also includes unfamiliar words that can be found in the glossary at the back of the book
Includ Color Illustrations,Glossary and Index
Keywords: Manners and customs -- Jamaica -- Social conditions